Development of an Arabic writing skills textbook based on collocations - Achmad Tito Rusady; Rizki Gumliar (Universitas Muhammadiyah Malang, 2024)
This study aims to develop Arabic writing skills teaching materials based on collocations, assess their feasibility, and evaluate their effectiveness. Collocations are combinations of words that naturally and correctly go together according to the cultural norms of native speakers. This research and development utilized the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The study results revealed: (1) The Arabic writing skills teaching materials were developed with fourteen topics based on collocations, starting with short texts, presenting a column of collocating words, guided exercises conducted through discussions among students and/or with the lecturer, detailed explanations with examples from the Qur'an, hadith, and Arabic news, followed by exercises and concluded with motivational statements; (2) Feasibility was obtained from expert validation and student feedback after field practice, with the data showing that the developed textbook is highly suitable for publication and teaching; (3) Effectiveness was determined by comparing pretest and posttest results, with statistical analysis using SPSS indicating a significant difference.